Liver Regeneration: Analysis of the Main Relevant Signaling Molecules - Yachao Tao; Menglan Wang; Enqiang Chen; Hong Tang (Hindawi Limited, 2017)
Liver regeneration is a highly organized tissue regrowth process and is the most important reaction of the liver to injury. The overall process of liver regeneration includes three phases: priming stage, proliferative phase, and termination phase. The initial step aims to induce hepatocytes to be sensitive to growth factors with the aid of some cytokines, including TNF-α and IL-6. The proliferation phase promotes hepatocytes to re-enter G1 with the stimulation of growth factors. While during the termination stage, hepatocytes will discontinue to proliferate to maintain normal liver mass and function. Except for cytokine- and growth factor-mediated pathways involved in regulating liver regeneration, new substances and technologies emerge to influence the regenerative process. Here, we reviewed novel and important signaling molecules involved in the process of liver regeneration to provide a cue for further research.